Leap of faith hubris, negligence, and America's greatest foreign policy tragedy - Mazarr, Michael J. 1965- (PublicAffairs, 2019)
"Leap of Faith is the first comprehensive and objective history of the decision to invade Iraq. Mike Mazarr shows how the most impressive and experienced foreign policy team made the greatest strategic folly of the century"--
Keywords: Golfkrieg -- 2003; USA; Iraq War (2003-2011); War on Terrorism (2001-2009); Iraq War, 2003-2011 / Causes; War on Terrorism, 2001-2009; United States / Foreign relations / 2001-2009; United States / Foreign relations / Iraq; Iraq / Foreign relations / United States; United States / Politics and government / 2001-2009; Iraq / Politics and government / 2003-; Diplomatic relations; Politics and government; War / Causes; Iraq; United States; Since 2001